Perceptions of Dentists in India Towards Transgender Patients: A Cross-Sectional Study - Logesh Sidhu; Priyadharshini Ragavane; Priyanga Chandrasekaran; Angeline Hephzibah Pauljoseph; Kavi Ashika; Vasanth Raj (Journal of Pharmacy and Bioallied Sciences)
Background: Transgender individuals face significant stigma and discrimination in healthcare, leading to adverse health outcomes. This study investigates the perceptions of dentists in India towards transgender patients. Methods: A cross-sectional study collected data from 143 licensed practicing dentists in India using a 9-item structured questionnaire distributed via online forms from November 2023 to January 2024. The questionnaire assessed dentists’ perceptions, comfort levels, and educational background regarding transgender healthcare. Results: The sample included 62.9% female and 37.1% male dentists, predominantly early-career practitioners. Only 32.2% had treated transgender patients, and 25.2% had received specific training in transgender health issues. Despite limited experience and training, 71.3% of dentists expressed a willingness to treat transgender patients, and 84% recognized the societal benefits of acknowledging transgender identities as natural. Additionally, 87.4% supported the inclusion of LGBTQ patients in healthcare. Significant barriers were noted, with many respondents acknowledging problematic attitudes among healthcare staff towards transgender individuals. Conclusions: The study highlights positive attitudes among dentists towards transgender patients, despite substantial gaps in training and experience. Addressing these gaps through targeted education and sensitization programs is crucial for fostering an inclusive healthcare environment. Future research should focus on longitudinal assessments and the effectiveness of educational interventions to enhance knowledge and attitudes toward transgender healthcare.